Facilitated Look-Back Analysis of Public Health Emergencies to Enhance Preparedness: A Brief Report of a Chemical Spill in Charleston, West Virginia. Issue 6 (November 2018) - Piltch-Loeb, Rachael; Savoia, Elena; Wright, Nasandra; Gupta, Rahul; Stoto, Michael A.
Abstract : To demonstrate how public health emergency systems can use health systems tools to analyze and learn from critical incidents, we employed a facilitated look-back approach to review the public response to a chemical spill in Charleston, West Virginia. We reviewed official reports, news articles, and other documents; conducted in-person interviews with key public health and emergency response officials and local community stakeholders; and organized a facilitated look-back meeting to identify root causes of the problems that were encountered. The primary response challenges were (1) public distrust stemming from scientific uncertainty about potential harms of chemicals involved in the spill and how this uncertainty was communicated and (2) communication within the public health system, broadly defined. We found that to address inherent uncertainty, health officials should acknowledge uncertainty and tell the public what is known and unknown, and what they are doing to get more information.